A Systematic Review of Digital Competence Evaluation in Higher Education - Juan-Antonio; Santiago Alonso-García; Blanca Berral-Ortiz; Juan-José Vi (MDPI AG, 2024)
University students' digital skills depend significantly on educators' proficiency, necessitating regular assessments. Tools like DigComp and the TPACK model are provided in this technological context. A systematic review, following PRISMA criteria, aims to evaluate digital competencies through globally used tools. DigCompEdu is prominent, with Spain leading the research, while unvalidated instruments from Asia highlight global disparities. This review will identify key tools and expose geographical and validation gaps, stressing the need for standardized assessments. Understanding the predominance of DigCompEdu and seeing the variation that is generated in Asia highlights the poor ability to transmit self-perceived competencies to learners.